1999
DOI: 10.1016/s0002-9440(10)65284-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor (VEGF)-Mediated Angiogenesis Is Associated with Enhanced Endothelial Cell Survival and Induction of Bcl-2 Expression

Abstract: Vascular endothelial growth factor (VEGF) is an endothelial cell mitogen and permeability factor that is potently angiogenic in vivo. We report here studies that suggest that VEGF potentiates angiogenesis in vivo and prolongs the survival of human dermal microvascular endothelial cells (HDMECs) in vitro by inducing expression of the anti-apoptotic protein Bcl-2. Growth-factor-enriched and serum-deficient cultures of HDMECs grown on collagen type I gels with VEGF exhibited a 4-fold and a 1.6-fold reduction, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
239
1
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 570 publications
(255 citation statements)
references
References 35 publications
12
239
1
3
Order By: Relevance
“…Furthermore, activation of iCaspase-9 was sufficient to induce apoptosis of endothelial cells in vivo resulting in ablation of human microvessels in immunodeficient mice. These results are consistent with previous observations that showed that factors such as VEGF promote endothelial cell survival by acting on various molecules including Bcl-2 and Akt, [2][3][4] that are known to function upstream of caspase-9 in the apoptosis pathway. 24 Most anti-angiogenic strategies currently in clinical trials are based on the delivery of antibodies or drugs that inhibit endothelial cell-specific survival signals and promote apoptosis by a default mechanism.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, activation of iCaspase-9 was sufficient to induce apoptosis of endothelial cells in vivo resulting in ablation of human microvessels in immunodeficient mice. These results are consistent with previous observations that showed that factors such as VEGF promote endothelial cell survival by acting on various molecules including Bcl-2 and Akt, [2][3][4] that are known to function upstream of caspase-9 in the apoptosis pathway. 24 Most anti-angiogenic strategies currently in clinical trials are based on the delivery of antibodies or drugs that inhibit endothelial cell-specific survival signals and promote apoptosis by a default mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore tested if apoptosis and caspase activation induced by iCaspase-9 could be affected by VEGF and bFGF, two potent antiapoptotic factors for endothelial cells in newly formed vessels. [3][4][5][6] In these experiments, we pre-incubated HDMEC-iCasp-9 with either VEGF or bFGF for 24 h, then added AP20187 and fresh VEGF or bFGF and measured the percentage of apoptotic cells after incubation with the dimerizer drug. Treatment of HDMEC-iCasp-9 with VEGF or bFGF did not have a significant effect on the levels of apoptosis triggered by induced dimerization of caspase-9 ( Figure 4a).…”
Section: Vegf or Bfgf Does Not Prevent Apoptosis Induced By Caspase-9mentioning
confidence: 99%
See 3 more Smart Citations